24-hour dietary recall method for use in adolescents in Burkina Faso - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Results from the validation study in Burkina Faso were published in Maternal & Child Nutrition. The authors conclude that based on the results, the 24‐hour dietary recall method can be used in adolescents to assess population dietary risk levels, changes in intakes over time and differences between groups.